Application of Fuzzy Analytical Hierarchy Process (FAHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in fast food restaurant location selection / Mohd Zul Fikri Mohd Zubir - Mohd Zubir, Mohd Zul Fikri (2021)
Location play an important role for fast food restaurant and affect their profitability so a lot of factors need to be considered before settling down at a specific places. In order to evaluate the most suitable location, method of fuzzy analytical hierarchy process is used. All of the factors are described in numerical values and their weightage are determined using Buckley’s geometric mean method. These weightage later incorporated into a decision matrix where the score of each alternatives location are calculated by using TOPSIS. From the result, the highest score is deemed to be the best location to launch a new fast food restaurant.